INFORMATION USE AND READING HABITS OF WORKING WOMEN IN THE STEEL CITY OF ROURKELA, INDIA - Panigrahi, Chittaranjan (Malaysian Journal of Library and Information Science, 1998)
Provides an insight into the reading habits, information needs and information seeking behavior of the working women of an Indian steel city, Roukela. Data collected through a structured questionnaire from 100 working women are analysed. The majority of the working women have stressed the need for an adequate and varied reading materials.